2017
DOI: 10.1002/cphc.201700973
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Flow MAS NMR Spectroscopy and Synchrotron PDF Analyses of the Local Response of the Brønsted Acidic Site in SAPO‐34 during Hydration at Elevated Temperatures

Abstract: In situ flow magic-angle spinning nuclear magnetic resonance (MAS NMR) spectroscopy and synchrotron-based pair distribution function (PDF) analyses were applied to study water's interactions with the Brønsted acidic site and the surrounding framework in the SAPO-34 catalyst at temperatures up to 300 °C for NMR spectroscopy and 700 °C for PDF. Si enrichment of the sample enabled detailed NMR spectroscopy investigations of the T-atom generating the Brønsted site. By NMR spectroscopy, we observed dehydration abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 47 publications
8
27
0
Order By: Relevance
“…In very recent study,K alantzopoulos et al found that the framework of molecular sieves become labile with subtle changes of Ta toms when interacting with water at 250-300 8 8C. [44] In the present work, aw ater-induced dynamic and reversible process of breaking and forming of T-O-T bonds is directly and definitely confirmed by using H 2 17 Of or hydrothermal treatment. Moreover,asevidenced in Figure 1a,the breaking and forming of T-O-T bonds becomes more easily to be realized in the H 2 17 Oa tmosphere at enhanced temperature,asisindicated that more 17 Oatoms from H 2 17 Ocan be incorporated into the molecular-sieve framework.…”
Section: Dynamic and Reversible T-o-t Bonds Breaking And Forming In Ssupporting
confidence: 72%
“…In very recent study,K alantzopoulos et al found that the framework of molecular sieves become labile with subtle changes of Ta toms when interacting with water at 250-300 8 8C. [44] In the present work, aw ater-induced dynamic and reversible process of breaking and forming of T-O-T bonds is directly and definitely confirmed by using H 2 17 Of or hydrothermal treatment. Moreover,asevidenced in Figure 1a,the breaking and forming of T-O-T bonds becomes more easily to be realized in the H 2 17 Oa tmosphere at enhanced temperature,asisindicated that more 17 Oatoms from H 2 17 Ocan be incorporated into the molecular-sieve framework.…”
Section: Dynamic and Reversible T-o-t Bonds Breaking And Forming In Ssupporting
confidence: 72%
“…Modern crystallographic techniques can integrate single crystal, powder, or neutron diffraction data with PDF analyses ,,. Such advances have fostered structural studies on disordered phases, (such as the recently reported liquid MOFs), dye‐zeolite materials, or catalysts under industrial conditions, unveiling, for example, the interaction of water with SAPO‐34 acidic sites and their environment at high temperature (700 °C) …”
Section: Characterization Techniquesmentioning
confidence: 99%
“…Another application is the desorption of surface-bound methanol from zeolites in the presence of water, for example after methane oxidation to methanol (Dyballa et al 2019a, b;Pappas et al 2017;Ravi et al 2017). The presence of bulk species and the interaction sites of water and methanol are also of interest for improving the stability of zeolites and related materials of different pore size, as the interaction sites like silanols can react with water at higher temperatures and damage the framework (Kalantzopoulos et al 2018(Kalantzopoulos et al , 2020Prodinger et al 2016).…”
Section: Introductionmentioning
confidence: 99%